Formação continuada do professor: um estudo das contribuições do Programa Conhecer para Acolher para a prática pedagógica inclusiva - VIEIRA, Scheilla de Castro Abbud (Universidade Federal do Pará, 2013)
This study is linked to the research line Curriculum and Teacher Formation of the Post Graduation Program of Science Education Institute of Federal Univesity of Pará. I defined as general objective analyze if the continued teacher formation, developed in the Program “Conhecer para Acolher: capacitação de educadores para atuar junto a alunos com necessidades educacionais especiais no contexto da escola regular da Rede Pública Estadual do Pará” give contributions of to the pedagogical practice of teachers in the inclusion process of students with special educational necessities in public state schools of Pará and as specifics objectives identify how the teachers articulate the vivenced in the formative process with their teaching action; evaluate which aspects of formation could have promoted (or not) their teaching action in the perspective of inclusion and investigate if the formative process have generate attitudinal changes in the teachers. The investigation configured itself as qualitative research of descriptive approach, supported on the theorists that discuss the teachers formation and inclusion, once I intend to comprise the educational phenomena and the continued formative period role to the ressignification of teacher actions in the construction process of the inclusive education. Were participants four teachers that have participate of the continued formative period of the reported Program, selected whereof following criteria: to have participate the first Program formation, occurred in 2002; to have participate of deepenment module; to have not participate of others formations about special education/inclusion; to have at the moment of the research student with special educational necessities in your classes. I have elect as data collection instruments the documental research and half-structured interview. Considering the research importance as possible auxiliary in continued formative periods for educational inclusion process of students with special necessities, for data analysis i have supported myself in the theoretical constructs that are vehiculated about inclusive education and I have search interface points between these constructs for the comprehension of complexity aspects that involve the teachers continued formative period process and it’s reflexes in their professional actuation. The data analysis allowed realize that formation have provided to teachers rethink their practices by assimilation and use of theoretical-practical concepts as resource for their action, when they affirmed that have activated more reflexive posture, more participative in their professional context; when they notice themselves as more sensitive to the differences that manifastates in their classrooms; when they appeal to distinct strategies to efectivate the educational process and realize themselves as co-responsible for the educational inclusion organization.